Experience of Sexual Violence among College Students: A Case Study of Kathmandu District - Karki, Tej Bahadur; Rawal, Bhagyashree (Nepal Journal of Multidisciplinary Research, 2023)
Sexual violence is a severe act of violence against human rights. There are multiple effects of sexual violence so it should be controlled everywhere. The study was conducted with the objective to explore the experience of sexual violence among college students of the Kathmandu district. The study was conducted among one public and one private college. A total of 60 students were selected for the study. It was based on the quantitative design. The study found that there was a significant difference between the boy and girl students regarding their experience of sexual violence because more boys felt forced to have sex than girls.